Building better research partnerships by understanding how Aboriginal health communities perceive and use data: a semistructured interview study. Issue 4 (25th April 2016) - Young, Christian; Tong, Allison; Sherriff, Simone; Kalucy, Deanna; Fernando, Peter; Muthayya, Sumithra; Craig, Jonathan C
Abstract : Objective: To describe the attitudes and beliefs of health professionals working in Aboriginal Community Controlled Health Services (ACCHS) towards the access, usage and potential value of routinely obtained clinical and research data. Design, setting and participants: Face-to-face, semistructured interviews were conducted with 35 health professionals from 2 urban and 1 regional ACCHS in New South Wales. The interviews were transcribed and themes were identified using an adapted grounded theory approach. Results: Six major themes were identified: occupational engagement (day-to-day relevance, contingent on professional capacity, emphasising clinical relevance), trust and assurance (protecting ownership, confidence in narratives, valuing local sources), motivation and empowerment (engaging the community, influencing morale, reassuring and encouraging clients), building research capacity (using cultural knowledge, promoting research aptitude, prioritising specific data), optimising service provision (necessity for sustainable services, guiding and improving services, supporting best practice), and enhancing usability (ensuring ease of comprehension, improving efficiency of data management, valuing accuracy and accessibility). Conclusions: Participants were willing to learn data handling procedures that could further enhance health service delivery and enable more ACCHS-led research, but busy workloads restrict these opportunities. Staff held concerns regarding the translation of research data into beneficial services, and believed that the outcome and purpose of data collection could be communicated more clearly. Promoting research partnerships, ensuring greater awareness of positive health data and the purposes of data collection, and communicating data in a user-friendly format are likely to encourage greater data use, build research capacity and improve health services within the Aboriginal community.